PENGARUH PENGGUNAAN E-COMMERCE, KUALITAS LAYANAN, DAN LITERASI KEUANGAN TERHADAP PENINGKATAN OMZET ONLINE SHOP DI KABUPATEN PONOROGO - Eka Tikasari; Nur Sayidatul Muntiah; Rizki Listyono Putro (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the effect of e-commerce usage, service quality, and financial literacy on increasing the turnover of online shops in Ponorogo Regency. This research is motivated by the gap between theoretical expectations, which suggest that these variables significantly improve business performance, and empirical conditions showing that online business actors have not optimally utilized these factors. This study employs a quantitative approach using primary data collected through questionnaires distributed to online shop owners in Ponorogo. The variables were measured using a Likert scale, and the data were analyzed using data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing both partially and simultaneously. The results indicate that e-commerce usage and financial literacy have a positive and significant effect on turnover increase, while service quality has a negative and significant effect. Simultaneously, all variables significantly influence turnover, contributing 63.6% to its variation. These findings suggest that digital technology utilization and financial management capability are key determinants in improving business performance, whereas service quality does not always play a dominant role in the online business context.